New Pandemic: Obesity and Associated Nephropathy - Sharma, Isha; Liao, Yingjun; Zheng, Xiaoping; Kanwar, Yashpal S. (Frontiers in Medicine, 2021)
Incidence of obesity related renal disorders have increased ten-folds in recent years. One of the consequences of obesity is an increased glomerular filtration rate (GFR) that leads to the enlargement of the renal glomerulus, i.e., glomerulomegaly. This heightened hyper-filtration in the setting of type 2 diabetes irreparably damages the kidney and leads to progression of end stage renal disease (ESRD). The patients suffering from type 2 diabetes have progressive proteinuria, and eventually one third of them develop chronic kidney disease (CKD) and ESRD. For ameliorating the progression of CKD, inhibitors of renin angiotensin aldosterone system (RAAS) seemed to be effective, but on a short-term basis only. Long term and stable treatment strategies like weight loss via restricted or hypo-caloric diet or bariatric surgery have yielded better promising results in terms of amelioration of proteinuria and maintenance of normal GFR. Body mass index (BMI) is considered as a traditional marker for the onset of obesity, but apparently, it is not a reliable indicator, and thus there is a need for more precise evaluation of regional fat distribution and amount of muscle mass. With respect to the pathogenesis, recent investigations have suggested perturbation in fatty acid and cholesterol metabolism as the critical mediators in ectopic renal lipid accumulation associated with inflammation, increased generation of ROS, RAAS activation and consequential tubulo-interstitial injury. This review summarizes the renewed approaches for the obesity assessment and evaluation of the pathogenesis of CKD, altered renal hemodynamics and potential therapeutic targets.